Viral RNA Targets and Their Small Molecule Ligands - Hermann, Thomas (RNA Therapeutics, 2017)
RNA genomes and transcripts of viruses contain conserved structured motifs which are attractive targets for small molecule inhibitors of viral replication. Ligand binding affects conformational states, stability, and interactions of these viral RNA targets which play key roles in the infection process. Inhibition of viral RNA function by small molecule ligands has been extensively studied for human immunodeficiency virus (HIV) and hepatitis C virus (HCV) which provide valuable insight for the future exploration of RNA targets in other viral pathogens including severe respiratory syndrome coronavirus (SARS CoV), influenza A, and insect-borne flaviviruses (Dengue, Zika, and West Nile) as well as filoviruses (Ebola and Marburg). Here, I will review recent progress on the discovery and design of small molecule ligands targeting structured viral RNA motifs.